Identifying Gaps in the Performance of Pediatric Trainees Who Receive Marginal/Unsatisfactory Ratings. (January 2018) - Li, Su-Ting T.; Tancredi, Daniel J.; Schwartz, Alan; Guillot, Ann; Burke, Ann; Trimm, R. Franklin; Guralnick, Susan; Mahan, John D.; Gifford, Kimberly A.
Abstract : Purpose: To perform a derivation study to determine in which subcompetencies marginal/unsatisfactory pediatric residents had the greatest deficits compared with their satisfactorily performing peers and which subcompetencies best discriminated between marginal/unsatisfactory and satisfactorily performing residents. Method: Multi-institutional cohort study of all 21 milestones (rated on four or five levels) reported to the Accreditation Council for Graduate Medical Education, and global marginal/unsatisfactory versus satisfactory performance reported to the American Board of Pediatrics. Data were gathered in 2013–2014. For each level of training (postgraduate year [PGY] 1, 2, and 3), mean differences between milestone levels of residents with marginal/unsatisfactory and satisfactory performance adjusted for clustering by program and C-statistics (area under receiver operating characteristic curve) were calculated. A Bonferroni-corrected significance threshold of .0007963 was used to account for multiple comparisons. Results: Milestone and overall performance evaluations for 1, 704 pediatric residents in 41 programs were obtained. For PGY1s, two subcompetencies had almost a one-point difference in milestone levels between marginal/unsatisfactory and satisfactory trainees and outstanding discrimination (≥ 0.90): organize/prioritize (0.93; C-statistic: 0.91) and transfer of care (0.97; C-statistic: 0.90). The largest difference between marginal/unsatisfactory and satisfactory PGY2s was trustworthiness (0.78). The largest differences between marginal/unsatisfactory and satisfactory PGY3s were ethical behavior (1.17), incorporating feedback (1.03), and professionalization (0.96). For PGY2s and PGY3s, no subcompetencies had outstanding discrimination. Conclusions: Marginal/unsatisfactory pediatric residents had different subcompetency gaps at different training levels. While PGY1s may have global deficits, senior residents may have different performance deficiencies requiring individualized counseling and targeted performance improvement plans. Abstract : Supplemental Digital Content is available in the text.